2014
DOI: 10.1039/c4tb00284a
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Ir(iii) complexes with styryl-BODIPY ligands showing near IR absorption/emission: preparation, study of photophysical properties and application as photodynamic/luminescence imaging materials

Abstract: Heteroleptic C^N cyclometalated iridium(iii) complexes showing strong NIR absorption were prepared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(82 citation statements)
references
References 119 publications
1
81
0
Order By: Relevance
“…The singlet‐oxygen quantum yield ( φ Δ ) of the photosensitizers has been used as a criterion to evaluate the relative efficacy of different photocatalysts. The singlet‐oxygen quantum yields of the free‐base porphyrins and the molecular complexes determined relative to that of methylene blue ( φ Δ = 0.57) using DPBF as the singlet‐oxygen quencher are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The singlet‐oxygen quantum yield ( φ Δ ) of the photosensitizers has been used as a criterion to evaluate the relative efficacy of different photocatalysts. The singlet‐oxygen quantum yields of the free‐base porphyrins and the molecular complexes determined relative to that of methylene blue ( φ Δ = 0.57) using DPBF as the singlet‐oxygen quencher are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…Singlet‐Oxygen Quantum‐Yield Measurements: The quantum yield of the singlet‐oxygen formation of the photosensitizers was measured by using 1,3‐diphenylisobenzofuran (DPBF) as the quencher of singlet oxygen and methylene blue ( φ Δ = 0.57 in dichloromethane) as a reference photosensitizer . The equation proposed by Murata et al[23c] [ Φ Δ = Φ Δ std (υ i × I std /υ i std × I )] was used to evaluate the φ Δ values. In a control reaction it was found that exposure of the dichloromethane solution of DPBF (8.0 × 10 –4 m ) to the 10 W red LED lamp led to no detectable degradation of DPBF (Supporting Information, S8).…”
Section: Methodsmentioning
confidence: 99%
“…Triplet‐triplet annihilation (TTA) with multi‐chromophores system comprising a triplet sensitizer and an acceptor is an effective approach to generating upconverted fluorescence using low‐power laser (<100 mW/cm 2 , equal to the sunlight), which was firstly demonstrated by Parker and Hatchard in 1962 and has significant applications so far, such as photovoltaics, photocatalysis and bioimaging . According to the revealed mechanism, TTA‐upconversion undergoes a series of multiple quantum processes: (i) the sensitizer first absorbs one photon to the excited singlet state and goes across its triplet excited state by intersystem crossing (ISC); (ii) then, the triplet–triplet energy transfer (TTET) occurs from the sensitizer to the acceptor, and then two triplet acceptors undergo the triplet‐triplet annihilation (TTA) with the result that photon‐upconversion is produced.…”
Section: Main Textmentioning
confidence: 99%
“…However, due to the weak absorption in visible light regions, the applications of iridium(III) complexes in the emerging TTA upconversion technology have been intensely limited. In order to tackle the disadvantage of iridium(III) sensitizer in TTA upconversion, it's a compromise approach to modify the chelating ligands by incorporating light‐harvesting groups, such as diketopyrrolopyrrole (DPP), naphthalenediimide (NDI) group, coumarin derivatives and boron dipyrromethene (BODIPY) . Recently, Duan et al also reported a novel iridium(III) sensitizer has moderate absorbance in visible light regions and exhibits excellent performance in upconversion studies .…”
Section: Main Textmentioning
confidence: 99%
“…In this respect, iridium complexes are ideal phosphorescent oxygen probes [18][19][20], and have been widely utilized to sense cellular oxygen or to image tumor hypoxia [21,22]. More recently, NIR phosphorescent iridium complexes have expanded their application as photodynamic therapy (PDT) agents [23][24][25]. Under light illumination, the interaction between molecular oxygen and excited MLCT states generates reactive singlet oxygen ( 1 O 2 ), which leads to cell death and tissue destruction.…”
Section: Introductionmentioning
confidence: 99%